Does political pressure on "gender" engender danger for scientific research? Evidence from a randomized controlled trial - Tünde Lénárd; Dániel Horn; Hubert János Kiss (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
We detect a significant negative effect of mentioning 'gender' as a research topic on conducting academic research in Hungary. Using a randomized information treatment involving a comprehensive sample of Hungarian education providers we find that they are less willing to cooperate in a gender related future research compared to a research without this specification. Our results also indicate that this negative sentiment is clearly against gender and not against any topic covering social inequalities in general.
Keywords: C90; C93; H39; I28; J16; 330; Randomized experiment; Gender; Information treatment